A 12 GHz wavelength spacing multi-wavelength laser source for wireless communication systems. (1st August 2017) - Peng, P.C.; Shiu, R.K.; Bitew, M.A.; Chang, T.L.; Lai, C.H.; Junior, J.I.
Highlights: The proposed scheme generates multi-wavelength with 12 GHz wavelength spacing. 84 optical carriers with a peak power fluctuation less than 2.21 dB are generated. The optical signal to noise ratio (OSNR) is about 14.4 dB. Our scheme is useful for wireless communication systems to support multiple users. Abstract: This paper presents a multi-wavelength laser source with 12 GHz wavelength spacing based on a single distributed feedback laser. A light wave generated from the distributed feedback laser is fed into a frequency shifter loop consisting of 50:50 coupler, dual-parallel Mach-Zehnder modulator, optical amplifier, optical filter, and polarization controller. The frequency of the input wavelength is shifted and then re-injected into the frequency shifter loop. By re-injecting the shifted wavelengths multiple times, we have generated 84 optical carriers with 12 GHz wavelength spacing and stable output power. For each channel, two wavelengths are modulated by a wireless data using the phase modulator and transmitted through a 25 km single mode fiber. In contrast to previously developed schemes, the proposed laser source does not incur DC bias drift problem. Moreover, it is a good candidate for radio-over-fiber systems to support multiple users using a single distributed feedback laser.